Machine-made sand tailing mud light non-sintered ceramsite as well as preparation method and application thereof

By utilizing the chemical activation reaction of manufactured sand tailings and fly ash and the decomposition pore mechanism of ammonium carbonate, the problems of high moisture content and clumping in the preparation of non-fired ceramsite were solved, achieving efficient and low-cost preparation of lightweight ceramsite and simplifying the process.

CN120864815APending Publication Date: 2025-10-31ZHEJIANG UNIV OF TECH

Patent Information

Application Number
CN202511077364.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-01
Publication Date
2025-10-31

AI Technical Summary

Technical Problem

The use of manufactured sand tailings and fly ash in the preparation of non-fired ceramsite presents problems such as high moisture content, clumping and stickiness, difficulty in mixing with other materials, low granulation efficiency, insufficient strength and excessive density. Furthermore, existing non-fired processes are complex and energy-intensive.

Method used

Using manufactured sand tailings, fly ash, cement, quicklime, and ammonium carbonate as raw materials, non-fired ceramsite is prepared through dehydration pretreatment, mixing, granulation with sodium silicate solution, and natural curing. The active oxides of fly ash react with alkaline substances to generate hydrated calcium silicate and hydrated calcium aluminate, which improves strength, and the density is reduced by generating pores through the decomposition of ammonium carbonate.

Benefits of technology

It simplifies the preparation process, reduces energy consumption and costs, improves the mechanical properties and granulation efficiency of ceramsite, meets the requirements of lightweight ceramsite, and has significant economic and environmental implications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120864815A_ABST
    Figure CN120864815A_ABST
Patent Text Reader

Abstract

The invention provides lightweight non-sintered ceramsite prepared from machine-made sand tailing mud as well as a preparation method and application of the lightweight non-sintered ceramsite, and relates to the field of lightweight building materials. The preparation method comprises the following steps: weighing the following raw materials in parts by weight: 50-65 parts of machine-made sand tailing mud, 35-50 parts of fly ash, 10-25 parts of cement, 16-19 parts of quick lime, 1-4 parts of ammonium carbonate and 12-18 parts of water; the method comprises the following steps: dehydrating and crushing the machine-made sand tailing mud, and stirring and mixing the materials in a round pot granulator to obtain an unfired ceramsite mixture; spraying the sodium silicate solution into a granulator at a constant speed to obtain spherical particles; and curing to obtain the light non-sintered ceramsite. The quick lime is used for pretreating the machine-made sand tailing mud, the water content of the machine-made sand tailing mud can be reduced, the machine-made sand tailing mud is successfully granulated, the strength of the ceramsite can be effectively improved, meanwhile, the ceramsite is combined with sodium silicate for alkali excitation, ammonium carbonate is used for foaming, preparation is simple, energy consumption is low, the solid waste utilization rate is high, and economic benefits are remarkable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of non-fired ceramsite technology, and relates to the field of lightweight building materials. Specifically, it relates to a type of lightweight non-fired ceramsite made from manufactured sand tailings, its preparation method, and its application. Background Technology

[0002] Tailings from manufactured sand production are solid waste generated during the production process, with an annual output of hundreds of millions of tons, and this output is increasing year by year. However, the overall utilization rate of manufactured sand tailings remains low. Currently, the main uses of manufactured sand tailings include roadbed backfilling and cement blending, but these methods can only handle a portion of the manufactured sand tailings nationwide. Fly ash is solid waste generated by coal-fired power plants, and its annual emissions are increasing year by year. Currently, the main uses of fly ash include concrete and building material production, but the overall utilization rate of fly ash also remains low. With the development of technology and the increasing environmental protection requirements, there is an urgent need to find a method for high-value treatment of tailings and fly ash. Under this trend, using manufactured sand tailings and fly ash to prepare non-fired ceramsite is a promising approach.

[0003] Firing is a traditional method for preparing lightweight ceramsite. For example, a method for firing lightweight ceramsite using subway waste soil and manufactured sand tailings, as disclosed in publication number "CN113307650A", uses subway waste soil and manufactured sand tailings as raw materials. After pretreatment, coarse aggregate is extracted and the sand content is controlled. Then, the moisture content of both is controlled at 35%~50%, and they are mixed with sodium oxide in a certain proportion. Sodium oxide is used to lower the melting point and generate gas. After stirring, the ceramsite preforms of a certain particle size are pressed on a two-roll extruder, and then fired in a kiln to obtain the finished ceramsite. For example, the method for producing lightweight ceramsite using river sludge and manufactured sand tailings, as disclosed in publication number "CN113248276A", uses river sludge and manufactured sand tailings as raw materials. The river sludge and manufactured sand tailings are pre-treated by water system equipment to extract coarse aggregates and control their sand content and moisture content. Then, sodium oxide is added and stirred according to a certain proportion. Sodium oxide is used to generate gas and lower the melting point. After stirring, ceramsite preforms of a certain particle size are pressed on a two-roll extruder and then fired in a kiln to obtain the finished ceramsite product. For example, the method for preparing lightweight ceramsite with sodium silicate surface sintering aid, disclosed in publication number "CN104291786B", involves stepwise spraying in a 5%~25% sodium silicate solution. During drying, sodium ions dissolved in water diffuse and accumulate on the surface shell of the raw material pellets. During firing, the sodium ions on the surface react with other substances to form fusible substances, acting as sintering aids. After firing, the finished ceramsite product is obtained. Compared with the traditional sintering method for preparing ceramsite, the preparation process and procedures are more complex. In particular, the kiln temperature needs to be raised to 1200℃ during the firing process, consuming a large amount of energy and emitting waste gas that pollutes the environment.

[0004] Obviously, compared with the firing method, the non-firing method for preparing lightweight ceramsite is more energy-efficient and environmentally friendly, and it is a convenient and low-cost solution for preparing lightweight ceramsite. For example, the non-firing ceramsite for iron tailings and its preparation method disclosed in CN112794666B involves ball milling the iron tailings to a particle size of less than 300 mesh, then disintegrating them under the action of a strong alkaline solution of sodium silicate and sodium hydroxide, releasing active ions that react with the alkaline components in the solution to generate gelling hydration products, forming an alkali-activated iron tailings gelling material matrix; simultaneously, sodium bicarbonate is added and decomposes during steam curing to generate carbon dioxide gas which is fixed in the matrix, ultimately forming porous non-firing ceramsite after curing. For example, the publication number "CN113200731B" discloses a solid waste-based non-fired high-strength ceramsite and its preparation method. Its core material includes the following components: phosphogypsum, sludge incineration ash, slag powder, Class III fly ash, cement, insulation board granules, and ammonium bicarbonate; the outer shell includes the following components: phosphogypsum, slag powder, cement, Class I fly ash, and silica fume. A two-stage curing process is employed: first, the core material is prepared; after initial curing, the core material is wrapped with the shell material, and surface modification is performed. Another example is the publication number "CN114057465B" which discloses a foamed non-fired ceramsite prepared from waste aluminum ash and iron tailings and its preparation method. Waste aluminum ash obtained after defluorination and denitrification pretreatment of secondary aluminum ash is mixed with iron tailings, cement, fly ash, activator, pore-forming agent, water glass, and water in a certain mass ratio. The mixture is then stirred, granulated, molded, aged, and steam-cured to obtain foamed non-fired ceramsite. However, the aforementioned methods for preparing non-fired ceramsite still have several problems and are difficult to directly and effectively apply to the research on preparing non-fired ceramsite from manufactured sand tailings and fly ash. For example, the solid waste-based non-fired high-strength ceramsite and its preparation method disclosed in "CN113200731B" require the preparation of a core material, initial curing, coating with an outer shell, secondary curing, and finally surface modification during the granulation stage, making the granulation process cumbersome. The foamed non-fired ceramsite and its preparation method prepared using waste aluminum ash and iron tailings disclosed in "CN114057465B" involve complex raw material pretreatment processes and high energy consumption during curing.

[0005] Currently, the non-fired granulation method using manufactured sand tailings often encounters the following problems: Because the tailings have a moisture content of approximately 23% before granulation pretreatment, they are clumpy and sticky, making them difficult to mix with other granulation raw materials such as fly ash. Furthermore, drying tailings, a cheap material, in a dryer wastes energy, which is inconsistent with green principles. Moreover, tailings as raw materials have low granulation efficiency during the granulation process, resulting in insufficient strength and excessive density after granulation. Therefore, how to effectively utilize manufactured sand tailings and fly ash to successfully prepare non-fired ceramsite remains a research topic in this field.

[0006] Based on this, the present invention is proposed. The non-fired ceramsite made from manufactured sand tailings and fly ash is prepared without firing during the ceramsite preparation process. It is made by mixing and granulating manufactured sand tailings and fly ash as the main raw materials, with the addition of additives, and is obtained through both natural curing and standard curing methods. Because fly ash is incorporated, its strength development mechanism is through chemical activation, which promotes the reaction of active oxides such as SiO2 and Al2O3 in the fly ash with alkaline substances, and then with Ca... 2+ The reaction produces hydrated calcium silicate (CSH) and hydrated calcium aluminate (CAH), hydraulic cementitious products that improve the mechanical properties of ceramsite. Since fly ash is mainly composed of SiO2 (approximately 51.63%) and Al2O3 (approximately 33.98%), it can also be used as a binder to improve the efficiency of preparing non-fired ceramsite. Compared to sintered ceramsite, non-fired ceramsite consumes far fewer resources and causes far less environmental pollution. Furthermore, the non-fired method for preparing ceramsite has low production costs, and the required raw materials are readily available, making it more promising for research and development. Moreover, this invention is very simple in terms of raw material pretreatment and granulation processes, and also has low maintenance costs, making it of significant economic importance. Summary of the Invention

[0007] In view of this, the present invention provides a lightweight non-fired ceramsite made from manufactured sand tailings, its preparation method and application, to solve the problems of consuming a large amount of energy and having a complicated preparation process when preparing ceramsite from manufactured sand tailings, and to make full use of solid waste and additives to improve the performance of non-fired ceramsite.

[0008] The technical solution adopted by the present invention to achieve the aforementioned technical objective is as follows: According to one aspect of the present invention, a method for preparing lightweight, non-fired ceramsite from manufactured sand tailings is provided, comprising: S1: Weigh the raw materials, which include, by weight, 50-65 parts of manufactured sand tailings, 35-50 parts of fly ash, 10-25 parts of cement, 16-19 parts of quicklime, 1-4 parts of ammonium carbonate and 12-18 parts of water. S2: The pretreatment of the manufactured sand tailings by dewatering and crushing before granulation is carried out to obtain pretreated powder. S3: Transfer all solid raw materials to a round pot granulator and stir to mix thoroughly to obtain non-fired ceramsite mixture; S4: Prepare a sodium silicate solution and spray the sodium silicate solution into a round pot granulator at a uniform speed through a spray bottle to prepare spherical particles; S5: Transfer the spherical particles for curing to obtain lightweight, non-fired ceramsite.

[0009] Preferably, the preparation environment temperature recommended by the present invention is ≥10℃, and the preparation environment humidity is ≤40%.

[0010] Preferably, the raw materials in step S1 include, by weight, 50 to 60 parts of manufactured sand tailings, 40 to 50 parts of fly ash, 10 to 25 parts of cement, 16 to 19 parts of quicklime, 1 to 4 parts of ammonium carbonate, and 12 to 18 parts of water.

[0011] Preferably, the mud content of the manufactured sand tailings in step S1 is not less than 60%, and the moisture content is not more than 25%; more preferably, the mud content is 60%-65%, and the moisture content is 20-23%; even more preferably, the mud content is 62.22%, and the moisture content is 22.55-23%, with a fineness of less than or equal to 2.36 mm. More preferably, the moisture content of conventional manufactured sand tailings is approximately 30%-40%, and it needs to be reduced to not more than 25% using physical methods such as extrusion. Commonly, in manufactured sand production plants, the moisture content of manufactured sand tailings is reduced to no more than 25% using simple roller extrusion. More preferably, the chemical composition of the manufactured sand tailings, by mass percentage, is as follows: SiO2 (45%~75%), Al2O3 (15%~35%), K2O (3%~10%), Fe2O3 (2%~10%), CaO (0.5%~5%), MgO (0.5%~3%). Even more preferably, the chemical composition is as follows: SiO2 (60%~65%), Al2O3 (20%~25%), K2O (3%~5%), Fe2O3 (3%~5%), CaO (1%~4%), MgO (1%~2.5%). Even more preferably, the chemical composition is as follows: SiO2 63.20%, Al2O3 21.31%, K2O 4.35%, Fe2O3 4.29%, CaO 2.43%, MgO 1.88%.

[0012] Preferably, the fly ash in step S1 is Class II fly ash. More preferably, the fly ash has the following chemical composition by mass percentage: SiO2 (40%~55%), Al2O3 (15%~35%), CaO (1%~10%), Fe2O3 (3%~15%), MgO (≤5%). Even more preferably, the chemical composition is as follows: SiO2 (45%~55%), Al2O3 (20%~35%), CaO (3%~5%), Fe2O3 (3%~6%), MgO (≤3%). Even more preferably, the chemical composition is as follows: SiO2 51.63%, Al2O3 33.98%, CaO 4.43%, Fe2O3 4.40%, MgO 1.16%.

[0013] Preferably, the cement is ordinary Portland cement, grade P•O 42.5. More preferably, the cement has the following chemical composition by mass percentage: CaO (55%~65%), SiO2 (20%~24%), Al2O3 (4%~7%), MgO (1%~5%), Fe2O3 (2%~5%). Even more preferably, the chemical composition is as follows: CaO (60%~65%), SiO2 (21%~23%), Al2O3 (4%~5%), MgO (3%~5%), Fe2O3 (2%~4%). Even more preferably, the chemical composition is as follows: CaO 62.04%, SiO2 22.07%, Al2O3 4.23%, MgO 4.01%, Fe2O3 3.04%.

[0014] Preferably, the quicklime is high-purity quicklime powder with a calcium content greater than or equal to 99%; and / or, the ammonium carbonate is ammonium carbonate powder.

[0015] Preferably, in step S1, the proportions of quicklime, manufactured sand tailings, and fly ash are as follows: quicklime accounts for 16% to 19% of the total mass of manufactured sand tailings and fly ash; and / or, the total weight of manufactured sand tailings and fly ash is 100 parts. It is particularly noted that, within the recommended environmental conditions, if the humidity is close to 40%, the amount of quicklime can be appropriately increased within the mixing ratio range. Adding less than 16% quicklime will make granulation difficult, while adding more than 19% will increase costs. Therefore, by adopting the above technical solution, this invention, while ensuring cost, can reduce the moisture content of manufactured sand tailings through the addition of quicklime to achieve successful granulation, and can also effectively improve the strength of ceramsite and promote the generation of ammonium carbonate gas.

[0016] Preferably, in step S2, the pretreatment involves thoroughly mixing the manufactured sand tailings and quicklime, then covering them with a film and allowing them to stand, followed by crushing the mixture into powder using a pulverizer. And / or, the film-coated standing time is 24~48h; And / or, the particle size of the powder is above 60 mesh; And / or, the moisture content of the powder is 8% to 10%.

[0017] Preferably, the stirring in step S3 is performed at a speed of 45-50 r / min for 5-10 min. More preferably, all solid raw materials are first thoroughly mixed to obtain a mixed powder before being transferred to a circular pot granulator for stirring; the solid raw materials include pretreated powder, fly ash, cement, and ammonium carbonate.

[0018] Preferably, the preparation of the sodium silicate solution in step S4 involves preparing a sodium silicate solution with a concentration of 0.082~0.328 mol / L and allowing it to stand to lower the temperature, preferably for 24 hours, and preferably in an environment of 20±2℃. The sodium silicate solution can react with the active oxides in the raw materials to improve strength. The granulator speed is 32~38 r / min. If the ambient humidity is greater than or equal to 30% and less than or equal to 40%, the granulator speed should be reduced to 30~32 r / min. More preferably, the uniform flow rate is 250 ml / h~280 ml / h.

[0019] Preferably, the curing process described in step S5 refers to curing in a dry curing room followed by curing in a standard curing room; more preferably, the spherical particles are cured in a dry curing room for 24 hours and then transferred to a standard curing room for 28 days. The temperature in the dry curing room is 20±1℃ and the humidity is 50±1%, while the temperature in the standard curing room is 20±0.5℃ and the humidity is greater than or equal to 95%.

[0020] It should be noted that the mixing ratio proposed in step S1 refers to the mixing ratio range recommended by the present invention. This mixing ratio range is proposed on the basis of ensuring granulation efficiency, granulation rate and maximizing the disposal of solid waste.

[0021] The present invention also provides a type of lightweight, non-fired ceramsite prepared by any of the above-mentioned preparation methods.

[0022] The present invention also provides an application of the lightweight, non-fired ceramsite prepared by any of the above preparation methods in the field of building materials.

[0023] In this invention, because fly ash is incorporated, the strength development mechanism is achieved through chemical activation, which promotes the reaction of active oxides such as SiO2 and Al2O3 in the fly ash with alkaline substances, and then with Ca... 2+ The reaction produces hydrated calcium silicate (CSH) and hydrated calcium aluminate (CAH), hydraulic cementitious products that improve the mechanical properties of the ceramsite. Since fly ash is mainly composed of Al2O3 and other substances, it can also be used as a binder to improve the efficiency of preparing non-fired ceramsite. Furthermore, this invention utilizes quicklime to reduce the moisture content of the tailings sludge before granulation, thereby increasing the strength of the ceramsite. Simultaneously, in step S3, ammonium carbonate, upon the addition of quicklime and sodium silicate solution, reacts with OH-... - After the reaction, it decomposes into CO2 and NH3 gases, creating pores inside the ceramsite and reducing its density.

[0024] The lightweight, non-fired ceramsite made from manufactured sand tailings and its preparation method provided by this invention have the following advantages compared with the prior art: This invention proposes a method for preparing non-fired ceramsite using manufactured sand tailings as raw material. The method utilizes quicklime to dry the manufactured sand tailings, facilitating granulation and improving the strength of the ceramsite. This eliminates the need for traditional methods involving drying materials in an oven and firing the ceramsite in a kiln, improving processing convenience, saving energy consumption, and reducing costs. Furthermore, the invention leverages alkali activation and the alkaline environment provided by quicklime to promote the generation of ammonium carbonate gas, facilitating foaming. This meets the requirement for reduced density in ceramsite and simplifies the preparation process through the synergistic effect between raw materials.

[0025] The preparation process of this invention is simple, saves time and costs, uses less cement, generates more solid waste, and does not require drying materials or kiln firing, thus saving economic costs, protecting the environment, and having significant economic importance. Attached Figure Description

[0026] Figure 1 This is a schematic diagram of the lightweight, non-fired ceramsite made from the manufactured sand tailings of the present invention and its preparation process.

[0027] Figure 2 This is a photograph of the actual product of the lightweight, non-fired ceramsite tailings from the machine-made sand of this invention. Detailed Implementation

[0028] To better clarify and understand the objectives, process solutions, and advantages of this invention, the technical solutions and implementation methods of this invention will be further described clearly, completely, and in detail below through specific embodiments and in conjunction with the accompanying drawings. It should be understood that the embodiments described in this invention are implemented under the premise of the technical solutions of this invention, providing detailed implementation methods and specific operating procedures, but are only some embodiments of this invention, not all embodiments. The specific implementation methods described are limited to illustrating and explaining this invention and do not limit this invention. Based on the embodiments of this invention, all other implementation methods obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0029] Unless otherwise specified, the experimental methods and conditions used in the embodiments of this invention are conventional methods and conditions. The materials, reagents, instruments, and equipment used in the embodiments, unless otherwise specified, are all conventional substances or equipment known to those skilled in the art and can be obtained commercially or prepared by conventional methods. The reaction conditions described in the invention's content can all achieve the stated reactions and obtain the desired products. Due to space limitations, some embodiments are listed below to further illustrate the advantages of the technical solution of this invention.

[0030] like Figure 1 As shown, this embodiment provides a lightweight, non-fired ceramsite made from manufactured sand tailings and its preparation method, which includes the following steps: S1: Take manufactured sand tailings with a moisture content reduced to no more than 25%, preferably 20% to 23%, by means of machine roller extrusion. S2: The recommended preparation environment temperature is greater than or equal to 10℃, and the recommended preparation environment humidity is less than or equal to 40%; S3: Weigh the raw materials according to the following parts by weight: 50-65 parts of sand-making tailings, 35-50 parts of fly ash, 10-25 parts of cement, 16-19 parts of quicklime, 1-4 parts of ammonium carbonate and 12-18 parts of water; more preferably, 50-60 parts of machine-made sand tailings, 40-50 parts of fly ash, 10-25 parts of cement, 16-19 parts of quicklime, 1-4 parts of ammonium carbonate and 12-18 parts of water; In this step, the manufactured sand tailings preferably have a mud content of 62.22%, a moisture content of 22.55%, and a fineness of less than or equal to 2.36 mm. The chemical composition of the manufactured sand tailings, by mass percentage, is as follows: SiO2 (45%~75%), Al2O3 (15%~35%), K2O (3%~10%), Fe2O3 (2%~10%), CaO (0.5%~5%), MgO (0.5%~3%). Ammonium carbonate, upon the addition of quicklime and sodium silicate solution, reacts with OH- - After the reaction, it decomposes into CO2 and NH3 gases, creating pores inside the ceramsite and reducing its density; The fly ash mentioned is Class II fly ash. Its strength development mechanism is through chemical activation, which promotes the reaction of active oxides such as SiO2 and Al2O3 in the fly ash with alkaline substances, and then with Ca... 2+ The reaction produces hydrated calcium silicate (CSH) and hydrated calcium aluminate (CAH) hydraulic cementitious products, which improve the mechanical properties of ceramsite. Since fly ash is mainly composed of substances such as Al2O3, it can also be used as a binder to improve the efficiency of preparing non-fired ceramsite. The chemical composition of fly ash by mass percentage is as follows: SiO2 (40%~55%), Al2O3 (15%~35%), CaO (1%~10%), Fe2O3 (3%~15%), MgO (≤5%). The cement is ordinary Portland cement, grade P•O 42.5; the chemical composition of the cement by mass percentage is as follows: CaO (55%~65%), SiO2 (20%~24%), Al2O3 (4%~7%), MgO (1%~5%), Fe2O3 (2%~5%). The quicklime mentioned is high-purity quicklime powder with a calcium content greater than or equal to 99%; Furthermore, the proportions of quicklime, manufactured sand tailings, and fly ash in the mix design should conform to the following: quicklime accounts for 16% to 19% of the total mass of manufactured sand tailings and fly ash; and / or, the total weight of manufactured sand tailings and fly ash is 100 parts. It should be specifically noted that, within the recommended environmental conditions, if the humidity is close to 40%, the amount of quicklime can be appropriately increased within the mix design range. S4: The manufactured sand tailings are pretreated by dewatering and crushing before granulation, and then all solid raw materials are thoroughly mixed. The untreated manufactured sand tailings used in this invention have a moisture content of 22.5%. To prepare non-fired ceramsite from the manufactured sand tailings using a granulator, the moisture content of the tailings must first be addressed. To reduce the moisture content so that the tailings can be mixed with other materials and easily granulated after grinding into powder, pretreatment is performed before ceramsite preparation. The tailings are thoroughly mixed with a certain proportion of quicklime using a mixer, then covered and allowed to stand for 24 hours. The mixture is then pulverized into powder using a pulverizer. The covering and standing time is 24 to 48 hours. The powder has a particle size of 60 mesh or larger and a moisture content of 8% to 10%. In this step, the pretreatment of the manufactured sand tailings includes: adding quicklime (16%~19% by mass) to the manufactured sand tailings based on the total mass of the manufactured sand tailings and fly ash, and stirring thoroughly at an ambient temperature of 20±2℃. After stirring, the mixture is covered with a film and allowed to stand for 24 hours. Then, it is placed in a pulverizer to pulverize the stirred manufactured sand tailings into powder. The particle size of the powder is above 60 mesh, and the moisture content of the powder is 8% to 10%. S5: Transfer the raw material powder of the non-fired ceramsite to a round pot granulator and stir to obtain the non-fired ceramsite mixture; In this step, the stirring is performed at a speed of 45~50 r / min for 5~10 min. S6: Prepare a sodium silicate solution and spray the sodium silicate solution into the granulator at a uniform speed through a spray bottle to prepare spherical particles; In this step, the sodium silicate solution can be prepared by the user with a concentration of 0.082~0.328 mol / L. After preparation, it needs to be allowed to cool down in an environment of 20±2℃ for 24 hours. This allows the active oxides in the raw materials to react with the alkaline substances, thereby increasing the strength. The granulator speed is 38 r / min. If the ambient humidity is greater than or equal to 30% and less than or equal to 40%, the granulator speed should be reduced to 30~32 r / min. S7: The spherical particles are transferred to a dry curing room for curing to obtain lightweight, non-fired ceramsite. In this step, the curing process involves transferring the spherical particles to a dry curing room for 24 hours, followed by 28 days of curing in a standard curing room. The dry curing room has a temperature of 20±1℃ and a humidity of 50±1%, while the standard curing room has a temperature of 20±0.5℃ and a humidity of ≥95%.

[0031] Based on the above Figure 1 The method for preparing lightweight, non-fired ceramsite from machine-made sand tailings, as shown in the following Examples 1-5 and Comparative Example 1, will be further described in detail to illustrate the lightweight, non-fired ceramsite from machine-made sand tailings, its preparation method, and its effects.

[0032] Example 1

[0033] This embodiment includes the following components in parts by weight: 50 parts of machine-made sand tailings (mixed thoroughly with 16 parts of quicklime and left to stand for 24 hours), 50 parts of Grade II fly ash, 15 parts of P•O 42.5 ordinary Portland cement, 3 parts of ammonium carbonate, and 1000 mL of sodium silicate solution with a concentration of 0.328 mol / L.

[0034] The above raw materials are mixed and added in sequence, granulated by a round pot granulator, and then cured in a dry curing room for 24 hours before being transferred to a standard curing room for 28 days to obtain non-fired ceramsite. The non-fired ceramsite is then tested.

[0035] Example 2

[0036] This embodiment includes the following components in parts by weight: 55 parts of machine-made sand tailings (mixed thoroughly with 16 parts of quicklime and left to stand for 24 hours), 45 parts of Grade II fly ash, 10 parts of P•O 42.5 ordinary Portland cement, 1 part of ammonium carbonate, and 1000 mL of sodium silicate solution with a concentration of 0.328 mol / L.

[0037] The above raw materials are mixed and added in sequence, granulated by a round pot granulator, and then cured in a dry curing room for 24 hours before being transferred to a standard curing room for 28 days to obtain non-fired ceramsite. The non-fired ceramsite is then tested.

[0038] Example 3

[0039] This embodiment includes the following components in parts by weight: 55 parts of machine-made sand tailings (mixed thoroughly with 19 parts of quicklime and left to stand for 24 hours), 45 parts of Grade II fly ash, 20 parts of P•O 42.5 ordinary Portland cement, 4 parts of ammonium carbonate, and 1000 mL of sodium silicate solution with a concentration of 0.328 mol / L.

[0040] The above raw materials are mixed and added in sequence, granulated by a round pot granulator, and then cured in a dry curing room for 24 hours before being transferred to a standard curing room for 28 days to obtain non-fired ceramsite. The non-fired ceramsite is then tested.

[0041] Example 4

[0042] This embodiment includes the following components in parts by weight: 60 parts of machine-made sand tailings (mixed thoroughly with 18 parts of quicklime and left to stand for 24 hours), 40 parts of Grade II fly ash, 25 parts of P•O 42.5 ordinary Portland cement, 1 part of ammonium carbonate, and 1000 mL of sodium silicate solution with a concentration of 0.328 mol / L.

[0043] The above raw materials are mixed and added in sequence, granulated by a round pot granulator, and then cured in a dry curing room for 24 hours before being transferred to a standard curing room for 28 days to obtain non-fired ceramsite. The non-fired ceramsite is then tested.

[0044] Example 5

[0045] This embodiment includes the following components in parts by weight: 65 parts of machine-made sand tailings (mixed thoroughly with 19 parts of quicklime and left to stand for 24 hours), 35 parts of Grade II fly ash, 20 parts of P•O 42.5 ordinary Portland cement, 1 part of ammonium carbonate, and 1000 mL of sodium silicate solution with a concentration of 0.328 mol / L.

[0046] The above raw materials are mixed and added in sequence, granulated by a round pot granulator, and then cured in a dry curing room for 24 hours before being transferred to a standard curing room for 28 days to obtain non-fired ceramsite. The non-fired ceramsite is then tested.

[0047] Compare with Example 1

[0048] This example includes the following components in parts by weight: 100 parts of Grade II fly ash, 10 parts of P•O 42.5 ordinary Portland cement, 2 parts of ammonium carbonate, and 1000 mL of sodium silicate solution with a concentration of 0.328 mol / L.

[0049] The above raw materials are mixed and added, and granulated using a round pot granulator. After curing in a dry curing room for 24 hours, the granules are transferred to a standard curing room for 28 days to obtain non-fired ceramsite. The non-fired ceramsite is then tested.

[0050] According to the national standard "Lightweight aggregates and their test methods - Part 2: Lightweight aggregates test methods" (GB / T17431.2-2010), the performance parameters of Examples 1-5 and Control Example 1 are shown in Table 1.

[0051]

[0052] The non-fired ceramsite prepared in the embodiments of the present invention meets the performance standards of lightweight aggregates in GB / T 17431.1-2010, and the lightweight aggregate has a low bulk density and meets the standard compressive strength, indicating that the present invention is a qualified lightweight non-fired ceramsite.

[0053] As can be seen, the method for preparing lightweight non-fired ceramsite from manufactured sand tailings proposed in this invention addresses the high moisture content of manufactured sand tailings by using quicklime for stirring. This reduces the moisture content of the manufactured sand tailings, facilitating granulation while improving the strength of the non-fired ceramsite. It eliminates the need for drying and kiln firing in traditional solutions, improving processing convenience and reducing processing costs. Furthermore, the alkalinity of quicklime and sodium silicate is used for alkaline activation, which promotes the generation of gas from ammonium carbonate under alkaline conditions, meeting the density requirements of lightweight ceramsite. Through the synergistic effect of various raw materials, lightweight non-fired ceramsite from solid waste is prepared.

[0054] Furthermore, based on the above-mentioned method for preparing lightweight non-fired ceramsite from manufactured sand tailings, it is shown that the non-fired ceramsite prepared by this invention has a low bulk density and excellent water absorption rate, indicating that the ceramsite has a large pore structure and can adsorb small particles and water in the environment. In addition to being used to prepare lightweight aggregate concrete, it can also be used as the core layer of permeable bricks in sponge cities, utilizing the excellent water absorption properties of ceramsite to enhance the purpose of water absorption and release in permeable bricks for sponge cities.

[0055] Those skilled in the art will understand that the features described in the various embodiments of the present invention can be combined in many ways. Even if such combinations are not explicitly described in the present invention, in particular, all combinations of the present invention fall within the scope of the present invention without departing from its guidance.

[0056] The embodiments of the present invention have been described above. However, these embodiments are merely illustrative and not intended to limit the scope of the invention. Various substitutions and modifications can be made by those skilled in the art without departing from the scope of the invention, and all such substitutions and modifications should fall within the scope of the invention.

Claims

1. A method for preparing lightweight, non-fired ceramsite from manufactured sand tailings, characterized in that, include: S1: Weigh the raw materials, which include, by weight, 50-65 parts of manufactured sand tailings, 35-50 parts of fly ash, 10-25 parts of cement, 16-19 parts of quicklime, 1-4 parts of ammonium carbonate and 12-18 parts of water. S2: The pretreatment of the manufactured sand tailings by dewatering and crushing before granulation is carried out to obtain pretreated powder. S3: Transfer all solid raw materials to a round pot granulator and stir to obtain non-fired ceramsite mixture; S4: Prepare a sodium silicate solution and spray the sodium silicate solution into a round pot granulator at a uniform speed to prepare spherical particles; S5: Curing the spherical particles yields lightweight, non-fired ceramsite.

2. The method for preparing lightweight, non-fired ceramsite from manufactured sand tailings according to claim 1, characterized in that, The manufactured sand tailings in step S1 have a mud content of not less than 60% and a moisture content of not more than 25%; the fly ash is Class II fly ash; the cement is ordinary Portland cement; and the quicklime is high-purity quicklime powder with a calcium content of not less than 99%.

3. The method for preparing lightweight, non-fired ceramsite from manufactured sand tailings according to claim 2, characterized in that, The chemical composition of the manufactured sand tailings, by mass percentage, is as follows: SiO2 (45%~75%), Al2O3 (15%~30%), K2O (3%~10%), Fe2O3 (2%~10%), CaO (0.5%~5%), MgO (0.5%~3%); the chemical composition of the fly ash, by mass percentage, is as follows: SiO2 (40%~55%), Al2O3 (15%~35%), CaO (1%~10%), Fe2O3 (3%~15%), MgO (≤5%); the chemical composition of the cement, by mass percentage, is as follows: CaO (55%~65%), SiO2 (20%~24%), Al2O3 (4%~7%), MgO (1%~5%), Fe2O3 (2%~5%).

4. The method for preparing lightweight, non-fired ceramsite from manufactured sand tailings according to claim 1, characterized in that, The recommended preparation environment temperature is ≥10℃, and the recommended preparation environment humidity is ≤40%.

5. The method for preparing lightweight, non-fired ceramsite from manufactured sand tailings according to claim 1, characterized in that... In step S1, the proportion of quicklime to manufactured sand tailings and fly ash is as follows: quicklime accounts for 16% to 19% of the total mass of manufactured sand tailings and fly ash; and / or, the total weight of manufactured sand tailings and fly ash is 100 parts.

6. The method for preparing lightweight, non-fired ceramsite from manufactured sand tailings according to claim 1, characterized in that, In step S2, the pretreatment involves thoroughly mixing the manufactured sand tailings and quicklime, then covering it with a membrane and letting it stand, followed by crushing the mixture into powder using a pulverizer. And / or, the film-coated standing time is 24~48h; And / or, the particle size of the powder is above 60 mesh; And / or, the moisture content of the powder is 8% to 10%.

7. The method for preparing lightweight, non-fired ceramsite from manufactured sand tailings according to claim 1, characterized in that, The stirring in step S3 is carried out at a speed of 45~50 r / min for 5~10 min; the preparation of sodium silicate solution in step S4 is to prepare a sodium silicate solution with a concentration of 0.082~0.328 mol / L and let it stand, and the speed of the granulator is 32~38 r / min.

8. The method for preparing lightweight, non-fired ceramsite from manufactured sand tailings according to claim 1, characterized in that, The curing process described in step S5 involves moving the spherical particles to a dry curing room for curing and then transferring them to a standard curing room for further curing.

9. A type of lightweight, non-fired ceramsite prepared by the preparation method according to any one of claims 1-8.

10. The application of the lightweight, non-fired ceramsite tailings as described in claim 9 in the field of building materials.

Citation Information

Patent Citations

  • A kind of lightweight ceramsite with sodium silicate surface aided sintering and preparation method thereof

    CN104291786B

  • A non-fired ceramsite for iron tailings and its preparation method

    CN112794666B

  • A solid waste-based non-fired high-strength ceramsite and its preparation method

    CN113200731B

  • Method for firing light ceramsite by utilizing river sludge and machine-made sand tailing mud

    CN113248276A

  • Method for firing light ceramsite by using metro spoil and machine-made sand tailing mud

    CN113307650A

Cited By

  • High-sludge light-weight hydrophobic ceramsite based on ecological floating bed base material and preparation method of high-sludge light-weight hydrophobic ceramsite

    CN121872756A